A Triode Device with a Gate Controllable Schottky Barrier: Germanium Nanowire Transistors and Their Applications. Issue 33 (2nd July 2019) - Lin, Che‐Yi; Chen, Chao‐Fu; Chang, Yuan‐Ming; Yang, Shih‐Hsien; Lee, Ko‐Chun; Wu, Wen‐Wei; Jian, Wen‐Bin; Lin, Yen‐Fu
Abstract: Electrical contacts often dominate charge transport properties at the nanoscale because of considerable differences in nanoelectronic device interfaces arising from unique geometric and electrostatic features. Transistors with a tunable Schottky barrier between the metal and semiconductor interface might simplify circuit design. Here, germanium nanowire (Ge NW) transistors with Cu3 Ge as source/drain contacts formed by both buffered oxide etching treatments and rapid thermal annealing are reported. The transistors based on this Cu3 Ge/Ge/Cu3 Ge heterostructure show ambipolar transistor behavior with a large on/off current ratio of more than 10 5 and 10 3 for the hole and electron regimes at room temperature, respectively. Investigations of temperature‐dependent transport properties and low‐frequency current fluctuations reveal that the tunable effective Schottky barriers of the Ge NW transistors accounted for the ambipolar behaviors. It is further shown that this ambipolarity can be used to realize binary‐signal and data‐storage functions, which greatly simplify circuit design compared with conventional technologies. Abstract : Nanowire (NW) transistors based on a Cu3 Ge/Ge/Cu3 Ge heterostructure show ambipolar transport behavior with large current modulation. Quasistatic and dynamic electrical measurements indicate that the ambipolarity arises from the formation of tunable barriers. The transistor is used to realize both binary‐signal and data‐storage functions. This work offers a valuable direction for creating future electronics based on NW transistors.